« Je me contenterais bien d’une seule maladie » : penser et vivre son cancer en contexte polypathologique - Annick Tijou Traoré; Béatrice Jacques (Anthropologie & Santé)
Living with and managing the co-existence of several diseases is a complex health situation that is becoming more and more frequent and that increases with age. It is very often in this health context that older people are led to experience cancer, a disease to which they are also particularly vulnerable. From a socio-anthropological perspective, this article explores how these people perceive, experience and manage their cancer in light of other chronic diseases, from the experience of the concomitance of their biological vulnerabilities. Most patients think and experience their cancer as a problem that is articulated with other health problems. Their experience of cancer is built in a dynamic where the diseases at stake are articulated, contradictory or synergistic, while relying on links between the daily life of the disease (care, physiology, medication, care work...) and the social activities of the patients (leisure activities, family...).